RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KEARSIPAN DI SMA PGRI 1 PADANG PROVINSI SUMATERA BARAT BERBASIS WEB - Syukhri Syukhri; Pita Gusmayeni (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The advancement of information technology has now developed so rapidly, information has spread to the digital era, namely information that was previously processed in conventional ways, is now being managed with computer technology. Likewise with the archive management system for incoming and outgoing mail. The large number of incoming and outgoing letters every day at SMA PGRI 1 Padang makes the Administration section find it difficult to find files because they are looking for data one by one so that it takes quite a long time to search for archives, even archives often cannot be found because of the large number of archives. Realizing this, the title of Archival Management Information System Design at SMA PGRI 1 Padang West Sumatra Province using the Web-based CodeIgniter framework is expected to facilitate the Administration in the process of searching and distributing archives in a short time. The system development method used in this design is the Waterfall method. Because it is web-based, this application has the ability, the admin can manage the user, the Administrative Staff can add, edit, delete and save incoming and outgoing mail, the Head of Administration and the Principal can search for incoming and outgoing mail and can print the periodic letter report. . The results obtained from the implementation of this archiving application are to facilitate the Administration section in the computerized process of filing incoming and outgoing mail so that it becomes more efficient.